The relationship between financial literacy and retirement plan in China - Wang, Zeqian (2019)
The research has investigated the relationship between the financial literacy rate and the retirement plan in China. In this research, quantitative research has been adopted as the research method to test whether they is a statistical relationship between the two research variables. In order to acquire quantitative data for test the research subject, questionnaire survey has been adopted as the instruction to collect quantitative data from target research population for testing the research questions. 340 respondents in China are invited to take part in the online questionnaire survey. The quantitative data collected with the questionnaire survey have been analysed with SPSS Statistics software. Through data analysis, this report has found that the overall financial literacy rate of Millennials in China is still low. Key reasons for justifying the low financial literacy rate of Millennials in China the lack of finance literacy education and the lack of accessing to financial information in market. Additionally, the findings of this research have also indicated that the financial literacy level of Chinese Millennials is affected by demographic factors. Specifically, this report has found that age and educational level are the key determinants of the financial literacy rate of Millennials in China. Finally, the research findings have also proved that there is a positive and significant relationship between the financial literacy levels of Chinese Millennials and the development of retirement plan. This research has provided some positive implications in terms of theoretical and practical levels. In terms of theoretical value, this research creates a new literature base and fills up the existing literature gap. In terms of practical value, this research has outlined the current financial literacy rate of Millennials in China, and provides practical implications for policy makers in China to improve the financial literacy level and to increase the involvement of Chinese Millennials in retirement plan. This research has implications Chinese government needs to strengthen financial literacy education for increase the financial literacy level of Chinese Millennials, which helps to increase the engagement level of Chinese Millennials in developing their retirement plans.